Studi Literatur Review: Faktor-Faktor Yang Dapat Meningkatkan Kinerja Keuangan - Raflesia, Shania; Kuang, Tan Ming (Universitas Muhammadiyah Metro, 2025)
The success of the company is an important thing that needs to be known because it is useful in making decisions for both internal and external parties. Therefore we need to understand what aspects can affect work results financially or what we call the company’s financial performance. This research was conducted to determine the factors that can improve the financial performance of companies listed on the Indonesian stock exchange. The research was conducted through literature studies by collecting literature articles related to company financial performance. Based on the results of the study, it is known that there are five variables that can improve the financial performance of companies listed on the Indonesian stock exchange, namely good corporate governance, intellectual capital, company size, corporate social responsibility (CSR), and capital structure